Reduction of CH4 and CO2 emissions from waste generation through the use of refuse derived fuel technology - Deffi Ayu Puspito Sari; Kun Nasython; Diki Surya Irawan; Dessy Fadiilah (Heliyon)
This research quantifies the emission reductions achieved by utilizing Refuse Derived Fuel (RDF) technology at the Tritih Lor landfill in Cilacap City. Over 25 years, the landfill is projected to emit approximately 2,325,788 kg of CH4 and 8,527,888 kg of CO2. Waste processed through Mechanical Biological Treatment (MBT) generates 439,200 kg of CH4 and 26,352 kg of N2O, along with emissions from electricity consumption amounting to 969,074 kg of CO2, 19.95 kg of CH4, and 10.97 kg of N2O. Although this study does not directly compare landfill and MBT emissions, RDF significantly reduces the volume of organic waste entering the landfill, thereby minimizing long-term emissions. Transportation and excavator operations contribute annual emissions of 27,209.46 kg of CO2, 1.1016 kg of CH4, and 0.22032 kg of N2O. Stabilized organic waste from MBT is repurposed as an energy substitute in a cement factory, leading to substantial annual reductions in greenhouse gas emissions: 39,037,412 kg of CO2, 6 kg of CH4, and 537 kg of N2O.